Studies on Removal of Hexavalent Chromium Ion from Aqueous Solution Using Polyaniline Composite - Al-kinani, Emad M (Al-Nahrain Journal of Science, 2018)
Polyaniline (PANI) composites were prepared by polymerization of aniline in acidic medium using ammonium persulphate as initiator in the presence of Kaoline (PANK) and Bentonite (PANP). The pure PANI and their polyaniline composites were characterized by FTIR and Scanning Electron Microscope respectively. The SEM images have clearly shown the formation of polyaniline composites. The composites were used to removal of Cr(VI) ion pollutants from aqueous solutions. The equilibrium time increases with initial Cr(VI) concentration. experimental data are in good coincidence with Langmuir and Freundlich adsorption isotherm models, and have shown a good fitting to the experimental data. Adsorption of Cr(VI) obeys pseudo-second order equation with good correlation.